Bildedonasjoner og donatorbilder. Lekfolks gaver til kirken som visuell kultur - Stang, Margrethe C. (Collegium Medievale, 2016)
The article discusses donor images and testamentary donations of lights, furnishings and art to the Church in medieval Norway. A number of testaments, mentioning different types of visual donations, are discussed, as well as two visual sources: the altar frontal in Volbu church and the (now lost) wall paintings of Vang church. The Volbu frontal depicts four men kneeling in front of a statue of St. Blaise, probably representing a group of Volbu parishioners. The author suggests that the lost paintings of Vang, documented in watercolour in the 19th century, can be linked to the knight Sigvat of Leirhol. While all other Norwegian donor images have been lost, the written evidence supports the article's claim that not only visual donations, but also donor images, were prevalent in medieval Norway.